2019
DOI: 10.1111/obr.12909
|View full text |Cite
|
Sign up to set email alerts
|

The effectiveness of wearable technologies as physical activity interventions in weight control: A systematic review and meta‐analysis of randomized controlled trials

Abstract: Wearable technologies represent a novel approach in the prevention of obesity and overweight that encourages users to engage in physical activities aided by technological assistance. This is the first meta-analysis to investigate the effects of wearable technologies as physical activity interventions on weight control. Various electronic databases were searched to select eligible articles, including EBSCO, ScienceDirect, and PubMed, from the first available date to January 9, 2019. All analyses were performed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
56
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 66 publications
(59 citation statements)
references
References 28 publications
2
56
1
Order By: Relevance
“…Digital health approaches have flourished in the past decade. As found in numerous reviews, interventions using technology-based modalities (17)(18)(19), including SMS (20), apps (21,22), wearables (23,24), and websites (25), often produce weight loss similar to or less than that of in-person interventions but better than that of control arms; however, these reviews did not focus on self-monitoring. The seminal review that examined self-monitoring by Burke et al included studies published up to 2009 and found that greater engagement in selfmonitoring is associated with greater weight loss (26).…”
Section: Clinical Trials and Investigationsmentioning
confidence: 99%
“…Digital health approaches have flourished in the past decade. As found in numerous reviews, interventions using technology-based modalities (17)(18)(19), including SMS (20), apps (21,22), wearables (23,24), and websites (25), often produce weight loss similar to or less than that of in-person interventions but better than that of control arms; however, these reviews did not focus on self-monitoring. The seminal review that examined self-monitoring by Burke et al included studies published up to 2009 and found that greater engagement in selfmonitoring is associated with greater weight loss (26).…”
Section: Clinical Trials and Investigationsmentioning
confidence: 99%
“…As random effects, we had intercepts for subjects as well as by-subject random slopes for the effect of time. We used 6 months of data, with the origin of the time variable (week) set at week 4 (posthoc decision), for 2 main reasons: the likelihood of observing weight changes due to the intervention would be higher at 4 weeks rather than before (given that weight loss increases with intervention duration [36]) and the amount of missing data was minimal during the first month of the intervention, allowing for a more robust model [37]. P values were obtained by using likelihood ratio tests of the full model with the effect in question against the model without it.…”
Section: Discussionmentioning
confidence: 99%
“…The advent of wearable technologies, which encourages users to engage in PA and provides useful information for personalized care, has also positively influenced the prevention of overweight and obesity. Different studies have been conducted in this field [ 19 ], some of which demonstrate the effectiveness of wearables in weight control [ 20 ].…”
Section: Related Workmentioning
confidence: 99%